UTAGASI INOVASI PEMBELAJARAN TAJWID MELALUI MEDIA UTAGASI (ULAR TANGGA EDUKASI) DALAM MENINGKATKAN MOTIVASI DAN KEAKTIFAN BELAJAR SANTRI DI TPQ ROUDHOTUT THALIBIN - Fadli, Muntaqo; Nur Febriana, Finta; Khasanah, Taufiqoh; Nur Ilham, Muhammad; Rahmawati, Ferida (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Tajwid learning in Qur’anic educational institutions (TPQ) is generally dominated by memorization and repetition methods, which may lead to student boredom and low participation in the learning process. This condition highlights the need for innovative learning media that can create a more engaging and participatory learning environment. This study aims to describe the condition of tajwid learning before the implementation of the UTAGASI (Educational Snakes and Ladders Game) media, explain its implementation process, and analyze its impact on students’ learning motivation, learning activeness, and understanding of tajwid at TPQ Roudhotut Thalibin. This study employed a qualitative descriptive approach. The research participants consisted of one teacher and 15 students. Data were collected through observation, semi-structured interviews, and documentation. The data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation and technique triangulation. The findings revealed that the implementation of UTAGASI created a more interactive, enjoyable, and student-centered learning environment. The media enhanced students’ learning motivation through elements of challenge, collaboration, and immediate feedback, increased their active participation in discussions, question-answer activities, and classroom interactions, and improved their understanding of tajwid through contextual and meaningful repetition of learning materials. The novelty of this study lies in the integration of educational games, collaborative learning, and tajwid concept reinforcement within a single learning activity. The study suggests that educational game-based media can serve as an effective alternative for supporting more participatory and meaningful Qur’anic learning in TPQ settings.